2018
DOI: 10.1186/s12913-018-3553-4
|View full text |Cite
|
Sign up to set email alerts
|

Significant reductions in tertiary hospital encounters and less travel for families after implementation of Paediatric Care Coordination in Australia

Abstract: BackgroundOver a third of Australian children have long-term health conditions, often involving multiple organ systems and resulting in complex health care needs. Our healthcare system struggles to meet their needs because of sectoral fragmentation and episodic models of care. Children with medical complexity (CMC) currently rely on tertiary paediatric hospitals for most of their healthcare, but this is not sustainable. We evaluated the impacts of Care Coordination on tertiary hospital service use and family o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 13 publications
0
67
0
1
Order By: Relevance
“…Care co-ordination involving links with local general practitioners and access to a 24-h hotline has been shown to reduce subsequent encounters with tertiary hospitals, save on travel and reduce school absence. 28 Our findings of lower prevalence of admissions overall, and by category, among children from the most disadvantaged areas and those living in regional and remote areas may be explained by 24.0 †At first admission with chronic condition identified. ‡ Socio-economic disadvantage measured using geographic-based Index of Relative Socioeconomic Disadvantage, determined from postcode of residence.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Care co-ordination involving links with local general practitioners and access to a 24-h hotline has been shown to reduce subsequent encounters with tertiary hospitals, save on travel and reduce school absence. 28 Our findings of lower prevalence of admissions overall, and by category, among children from the most disadvantaged areas and those living in regional and remote areas may be explained by 24.0 †At first admission with chronic condition identified. ‡ Socio-economic disadvantage measured using geographic-based Index of Relative Socioeconomic Disadvantage, determined from postcode of residence.…”
Section: Discussionmentioning
confidence: 79%
“…Managed care plans may also provide a strategy to reduce admissions for children with such conditions. Care co‐ordination involving links with local general practitioners and access to a 24‐h hotline has been shown to reduce subsequent encounters with tertiary hospitals, save on travel and reduce school absence 28 …”
Section: Discussionmentioning
confidence: 99%
“…There is a clear psychological impact on the whole family which needs to be core to the preparation and support parents receive. 25,30 In Canada and the United States, models of care for children with medical complexity are being tested in which care coordination is provided. 31 In the UK, community paediatricians and palliative care often help with co-ordination of care and the charity Well Child funds nurses who help with co-ordinating care, day-today emotional and practical support and also help train parents and carers, but these services need expanding.…”
Section: Support For Parentsmentioning
confidence: 99%
“…Our findings on ED attendance contrast with recent observational studies that have shown up to a 40% decrease in ED presentations for children with medical complexity. 53 This review highlights important concerns about the design and evaluation of children's integrated care. Information regarding the design of integrated interventions in the articles included in this review is limited because no studies presented or described the use of logic models to inform complex intervention development, which have been shown to improve intervention efficiency 54,55…”
Section: Discussionmentioning
confidence: 99%